Reduction in Pain and Inflammation Associated With Chronic Low Back Pain With the Use of the Medical Food Theramine. (November 2016) - Shell, William E.; Pavlik, Stephanie; Roth, Brandon; Silver, Michael; Breitstein, Mira L.; May, Lawrence; Silver, David
Abstract : Management of chronic back pain is a challenge for physicians. Although standard treatments exert a modest effect, they are associated with narcotic addiction and serious side effects from nonsteroidal antiinflammatory agents. Moreover, neurotransmitter depletion from both the pain syndrome and therapy may contribute to a poor treatment outcome. Neurotransmitter deficiency may be related both to increased turnover rate and inadequate neurotransmitter precursors from the diet, particularly for essential and semi-essential amino acids. Theramine, an amino acid blend 68405-1 (AAB), is a physician-prescribed only medical food. It contains neurotransmitter precursors and systems for increasing production and preventing attenuation of neurotransmitters. A double-blind controlled study of AAB, low-dose ibuprofen, and the coadministration of the 2 agents were performed. The primary end points included the Roland Morris index and Oswestry disability scale. The cohort included 122 patients aged between 18 and 75 years. The patients were randomized to 1 of 3 groups: AAB alone, ibuprofen alone, and the coadministration of the 2 agents. In addition, C-reactive protein, interleukin 6, and plasma amino acid concentrations were measured at baseline and 28 days time points. After treatment, the Oswestry Disability Index worsened by 4.52% in the ibuprofen group, improved 41.91% in the AAB group, and improved 62.15% in the combination group. The Roland Morris Index worsened by 0.73% in the ibuprofen group, improved by 50.3% in the AAB group, and improved 63.1% in the combination group. C-reactive protein in the ibuprofen group increased by 60.1%, decreased by 47.1% in the AAB group, and decreased by 36% in the combination group. Similar changes were seen in interleukin 6. Arginine, serine, histidine, and tryptophan levels were substantially reduced before treatment in the chronic pain syndrome and increased toward normal during treatment. There was a direct correlation between improvement in amino acid concentration and treatment response. Treatment with amino acid precursors was associated with substantial improvement in chronic back pain, reduction in inflammation, and improvement in back pain correlated with increased amino acid precursors to neurotransmitters in blood.